Estudio de recepción del periódico comunitario El Chulla Quiteño. - Tapia Arcos, Laura Pamela (2016)
The research focuses its study on the reception of the community newspaper “El Chulla Quiteño” and the product acceptance in the community. From this, is taken into account the classic interrogations; what does the media do with the community and what does the community do with the media. In 2014, I performed my pre professionals practices in the Zonal Central Administration “Manuela Saenz”. At that period of time, it called my attention the project that the Department of Social Communication exerts with the downtown community through the newspaper “El Chulla Quiteño”. Since that moment, I pose this topic of research as a contribution to the municipal institution. And also, as a proposal that recognizes the role of the alternative media and the media in the community, as a tool that can promote social dialogue. The first part of the research deals with a theoretical systematization about the reception of studies, and a bibliographic review of the different investigations related to the topic raised in Latin America and Ecuador. In this same section, the importance of reception studies from the authors Guillermo Orozco, Jesús Martín Barbero, among others is been discussed. To end this first phase, I realized a non exhaustive content analysis of the newspaper “El Chulla Quiteño”, since its inception to its current publication. In the second stage, it is showed the methodology used for the acquisition of results; surveys were raised to readers and community reports of “El Chulla”, as well as an interview with the editor of the media. And finally, the results on the acceptance of the community newspaper “El Chulla Quiteño” were analyzed and interpreted in the five sectors of the central jurisdiction.